Compare the assessment center (AC) in occupations with high and low task interdependence in the individual and team empowerment - narges sadat mortazavi; حمیدرضا عریضی; zohre moosavi (Allameh Tabataba'i University Press, 2017)
The purpose of this study was to investigate difference between dimension- based assessment center and task-based assessment center and training in the individual empowerment and team empowerment in the workplace. The current study was the quasi experimental research and participants in this study were 24 managers of industrial Company that who were selected through purposeful sample and according to Murphy & Myors's (1999) table. The instruments used in the study included the simulations exercises(Role play, Leaderless group discussion, Case study and Oral presentations) and Individual Empowerment Questionnaire (Speritzer,1995) and Team Empowerment Questionnaire (Kirkman & Rosen,1999 ). Data was analyzed using the Kruskal-Wallis test. The results of this study showed that there is a difference between dimension- based assessment center and task-based assessment center and training in the team empowerment. Also there is a difference between assessment center in occupations with high and low task interdependence in team empowerment.Keywords: Team empowerment- Individual empowerment- Assessment center(AC